DETERMINASI PENGHINDARAN PAJAK MELALUI DER, ROA, UKURAN PERUSAHAAN, DAN KARAKTERISTIK PERUSAHAAN PADA SEKTOR MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2021 – 2023 - Shintya Amelia; Sauh Hwee Teng; Yessy Natalie Diannesia Nainggolan Parhusip; Jhon Piter (Journal of Economic, Bussines and Accounting (COSTING), 2025)
That research plan for (1) Test along with develop existing theories regarding tax avoidance. (2) Find out more specifically about the phenomenon of tax avoidance, including motives, strategies and impacts on various parties. (3) For the Company, the results research can help in making decisions regarding optimal tax strategies. The Strategy used in this investigation is a commensurate approach with sample and population study types. Data gathering techniques use library study and survey techniques. And the data processing technique second hand statistical calculations. The conclusions of this inquiry are (1) This implementation was carried out on 40 manufactur establishment on the Indonesian Stock Exchange (BEI) with data from 2021 continuously 2023 with affect of DER, ROA, large enterprise also corporation characteristics in contact with shirking. (2) Supporting factors and The inhibiting factor for tax avoidance is that the increasingly complex structure of business and international transactions makes tax avoidance practices more sophisticated and difficult to detect and tax avoidance is often incomplete or difficult to access because it is sensitive. (3) The impact of tax avoidance is reduced state revenue from the tax sector, state budget imbalance, and experiencing a decline in reputation and facing pressure from consumers, investors and the public.